THE EFFECT OF MOTIVATION, REWARD AND WORK ENVIRONMENT TO COMMITMENT AND IMPACT ON PERFORMANCE (Study on Teachers and Staffs of SD Al Baitul Amien 01 and 02 Jember) - Hizbullah Muhib; Muhammad Firdaus; Kasiman Kasiman (MBA - Journal of Management and Business Aplication, 2019)
This study aims to determine the influence of motivation, reward and work environment on commitment and its impact on performance (Study on Teachers and Staffs at SD Al Baitul Amien 01 and 02 Jember). Data analysis technique used is the technique of analysis with Path method. The results showed that: (1) Motivation, reward, and workplace have a positive and significant impact on commitment performance (Study on Teachers and Staffs at SD Al Baitul Amien 01 and 02 Jember); (2) Motivation, reward, and workplace influence on positive and significant on performance (Study on Teachers and Staffs at SD Al Baitul Amien 01 and 02 Jember); (3) Motivation, reward, and workplace affect on positive and significant performance through commitment (Study on Teachers and Staffs at SD Al Baitul Amien 01 and 02 Jember).